Classical behaviour after a phase transition - Lombardo, F.C. (2001)
We analyze the onset of classical behaviour after a second-order phase transition by considering a scalar field theory in which the system-field interacts with its environment, represented both by further fields and by its own short-wavelength modes. Within our approximations we see that the long-wavelength modes have become classical by the time that the transition has been first implemented (the spinodal time). © 2001 Published by Elsevier Science B.V.